Implementasi Mata Kuliah Kewirausahaan Dan Pengantar Bisnis Dalam Meningkatkan Minat Entrepreneur Mahasiswa (Studi Mahasiswa FEBI UIN Jambi) - Ambok Pangiuk (Indonesian Journal of Islamic Economics and Business, 2019)
This paper aims to describe the influence of course business introduction and entrepreneurship to improve student’s interest to develop the business. The research question focused on the constraint, interest, and the lecturer’s strategies. Qualitative descriptive is used as a research method. Data were collected through observation, depth interviews, and documentation. The sampling method is purposive sampling with criteria students who have started their own businesses and the lecturers who taught the course business introduction and entrepreneurship. The results show the courses mentioned above have motivated students to develop their business but the main constraints are time management and funding access. The lecturer’s strategy is accompanied them in a field trip, interview with a successful entrepreneur, and encourage to make innovation for their product.